Antihypertensive drug-related problems in Vietnamese ambulatory care - Hoang Hai Nguyen; Le Anh Thu Vu; Minh-Hoang Tran; Hong Tham Pham (Scientific Reports)
Abstract Evidence of antihypertensive drug-related problems (aDRP) is limited in Asian ambulatory care. To better detect aDRP without causing alert fatigue, we investigated whether adding more antihypertensive agents was associated with increasing aDRP risk and factors associated with physician acceptance of aDRP correction. We conducted a cross-sectional study targeting ambulatory prescriptions of Vietnamese patients with hypertension who either received standard therapy (using two or fewer medications, SdT) or standard plus add-on therapy (using more than two medications, SdT + add-on). Primary and secondary outcomes were number of aDRP and correction ratio of aDRP. We used multivariable Poisson regression to estimate the incidence rate ratio (IRR) and 95% confidence interval (95%CI). We analyzed 221 cases (patient age of 64.1 ± 9.0 years, 51.1% being female). On average, patients with SdT and SdT + add-on had 1.6 ± 1.3 and 1.6 ± 1.5 aDRP, respectively. Compared to the SdT group, SdT + add-on group did not have a higher number of aDRP (IRR = 1.11, 95%CI 0.87–1.43, p = 0.393) or likelihood of aDRP correction (IRR = 0.97, 95%CI 0.86–1.09, p = 0.578). We found the following factors to be associated with aDRP correction: unnecessary indication (IRR = 1.98, 95%CI 1.39–2.81, p < 0.001), missing indication (IRR = 1.93, 95%CI 1.68–2.21, p < 0.001), major-to-contraindicated drug interaction (IRR = 1.74, 95%CI 1.39–2.18, p < 0.001), adverse effects (IRR = 1.71, 95%CI 1.26–2.31, p < 0.001), nonconformity indication (IRR = 1.66, 95%CI 1.44–1.92, p < 0.001), and administration (IRR = 1.45, 95%CI 1.26–1.67, p < 0.001). In conclusion, adding antihypertensive agents was not associated with a higher number of aDRP or likelihood of aDRP corrections. Physician acceptance of aDRP corrections could be strongly related to unnecessary/missing indication, major-to-contraindicated drug interaction, and adverse effects. These findings could improve DRP alerts and maximize treatment outcomes in Asian patients with hypertension.